On two new genera of Asian prawns previously assigned to Macrobrachium (Crustacea: Decapoda: Caridea: Palaemonidae) - Wowor, Daisy; Ng, Peter K. L. (Zootaxa, 2010)
Two new genera of palaemonid prawns are described from South and Southeast Asia. The new genera are allied to Macrobrachium Bate, 1868, but can easily be separated by having a slender and glabrous second pereiopod, a long fifth pereiopod which is distinctly longer than the second pereiopod, a bilobed posterolateral margin of the fifth abdominal pleurite, the presence of one or two pairs of plumose setae at the ventroposterior margin of the telson, the absence of anterior lobes on male thoracic sternite 8 and distinctly larger adult females than males. Arachnochium gen. nov. (type species Palaemon mirabilis Kemp, 1917), can be distinguished from Tenuipedium gen. nov. (type species Macrobrachium palaemonoides Holthuis, 1950) by having a relatively shorter branchiostegal groove running from the base of the hepatic spine to the antennal carapace margin below the antennal spine, and having plumose setae which are longer than the inner pair of spines on the ventroposterior margin of the telson.